Trust Management in Distributed Systems. - Li, Huaizhi; Singhal, Mukesh (Computer (00189162), 2007)
The article discusses the importance of trust management in distributed systems, such as peer-to-peer networks and mobile ad hoc networks. The authors look at the current research on trust management in distributed systems and explore some open research areas. The different models for describing trust management in distributed systems include public-key cryptography, the resurrecting duckling model, and the distributed trust model, all of which are described in the text. The article also discusses the properties of peer-to-peer distributed systems and mobile ad hoc systems, and then offer the best trust management models for both systems. Several tables are included in the text.